Implementation of Character Education in Forming Confident, Polite and Caring Character through Social Studies Learning at SMP Al-Hasib Malang Regency - Nailul Fauziyah; Nuris Shofatul Fikroh (STKIP Taman Siswa Bima, 2023)
Al-Hasib Junior High School is an educational institution that prioritizes student achievement, both in academic and non-academic fields. Therefore, it is expected that students educated in such schools have superior knowledge, intelligence and good morals. However, facts on the ground show that there are still bad attitudes and ethics towards teachers, such as disrespect and disrespect also still exist. In addition, students' confidence in socializing is also still lacking. This study aims to understand overall school policies that shape the social character of AL-Hasib Junior High School students in accordance with guidelines from the Ministry of Education and Culture, and also to explore how the implementation of character education is carried out to form responsible, polite and caring social character. The research method used is a qualitative approach with a qualitative descriptive type. The main sources of information involve the principal, student waka, curriculum waka, and Al-Hasib Junior High School students themselves. This research involves collecting data through observation, interviews, and documentation which will then be analyzed by organizing the data, reducing the data and drawing conclusions. As for the validity of the data, it is tested using triangulation techniques. The findings of the research show that school policies to shape social character start from the implementation of the school curriculum. Learning activities in the classroom and teaching teachers are also directed to implement and fulfill aspects that are in accordance with the guidelines of the Ministry of Education. Then it ends with the evaluation process. At the implementation stage, students apply social character both inside and outside the classroom. This is expected to be a recommendation for teachers in carrying out learning in the future. Teachers are expected to provide deeper instillation of character values in students. In this way, it is expected that students can have a comprehensive understanding in implementing character values that are integrated with their daily learning.